KEANEKARAGAMAN LUMUT EPIFIT PADA GYMNOSPERMAE DI KEBUN RAYA BOGOR - Fibo Adhitya; Nunik Sri Ariyanti; Nina Ratna Djuita (Floribunda, 2014)
Since researchs on diversity of epiphytic Bryophytes are more common observed on Angiospermae than those on Gymnospermae, this study was conducted to observe diversity of epiphytic Bryophytes on Gymnospermae in BBG. The Bryophytes samples were collected from Gymnosperms trees in Blok I which is Cycadaceae familly and those in Blok II which are the familly of Pinaceae, Araucariaceae, Gnetaceae dan Podocarpaceae. Only the trees have diameter ≥ 20 cm of trunk were sampled. Bryophytes were collected from the trunk base at 0–200 cm above the ground, at four cardinal direction (north, south, west, and east). In total 18 species of epiphytic Bryophytes were found, included 12 genera and 7 families. The family which had the highest number of species was Lejeuneaceae. The most common species on Gymnosperm trees in the Botanical Garden were Lejeunea tuberculosa and Octoblepharum albidum. Both of them were found at 6 trees of 13 total tree samples. The species were found more frequently at west (2,1%) and north (1,8%) part than east and south part of the host trees. They more frequently inhabit the trunk base on 0–100 cm than 100–200 cm.